Laser Beam Melting and heat-treatment of 1.2343 (AISI H11) tool steel - microstructure and mechanical properties - Huber, Florian; Bischof, Corinna; Hentschel, Oliver; Heberle, Johannes; Zettl, Julian; Nagulin, Konstantin Yu.; Schmidt, Michael (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2018)
Laser Beam Melting (LBM) of metals is an innovative additive manufacturing technology for producing complexly shaped parts. However, the spectrum of available materials is yet limited and the qualification of further alloys is subject of ongoing research. Considering tooling applications e.g. for injection moulding low alloyed tool steels like 1.2343 (AISI H11) would be of particular interest. The feasibility of processing 1.2343 by LBM has already been shown. Besides the LBM-process itself, also a heat-treatment process has to be taken into account. Heat-treatment is necessary to reduce the process-inherent internal stress and to adjust the desired mechanical properties. Hence, an experimental study on the heat-treatment of laser beam molten specimens made from 1.2343 is conducted. The resulting microstructure is characterised by metallographic microsections and electron backscatter diffraction (EBSD). Additionally, hardness measurements and tensile tests give information about the mechanical properties in dependence of the build direction and the heat-treatment strategy. The ultimate tensile strength after annealing reached 2148 ± 16 MPa along with an elongation at break of 8.8 ± 1.1 %. The hardness of the LBM-generated material was determined to 737 ± 16 HV1 after hardening and to 585 ± 9 HV1 after annealing.
Keywords: Additive Manufacturing; Laser Powder Bed Fusion; Heat-treatment; AISI H11 1.2343; Microstructure; Tensile strength